African contribution to Christendom - Adeyemo, Tokunboh (Scriptura, 1991)
In this article Christianity in Africa is deemed to be making six contributions to world Christianity. Although the church in Africa is poor, It has much to offer by way of its holistic world view, people-centeredness, and community orientation, expressive. Worship, adaptability in mission, and the will to cooperate. The latter is seen particularly in the flourishing of the ecumenical association of evangelicals in Africa.
free
Keywords: Africa – Church history